Integrasi Nilai-Nilai Islam dalam Kepemimpinan Pendidikan - Ika Kartika; Noerlitasari; Ade Maulana Saputra; Yuli Purwaningsih; Andri Yuningsih; Alimuddin; Swanggi Leman (Ikatan Dai Indonesia, 2025)
Islamic education holds a comprehensive orientation, emphasizing not only academic achievement but also the cultivation of noble character and personal development in line with Islamic values. In this regard, leadership in Islamic education plays a crucial role in shaping the vision and culture of institutions with Islamic character. This study explores how Islamic values are integrated into educational leadership practices. Employing a qualitative approach through library research, it examines conceptual frameworks and theories derived from classical and contemporary Islamic thought, as well as modern leadership models. The findings reveal that effective Islamic educational leadership integrates prophetic leadership principles (humanization, liberation, transcendence), transformational leadership grounded in Islamic ethics, and participatory leadership based on the concept of shura (consultation). Core values such as shiddiq (honesty), amanah (trustworthiness), tabligh (effective communication), fathanah (wisdom), and ‘adl (justice) are central to the leadership approach. The study also identifies key strategies for implementation, including value-based vision development, cultivating an Islamic organizational culture, leadership capacity-building programs, and comprehensive evaluation systems. Despite challenges from internal organizational resistance and external pressures of globalization, the integration of Islamic values into leadership has the potential to enhance the integrity, effectiveness, and holistic impact of educational institutions. This research contributes to the development of a contextually relevant Islamic educational leadership model responsive to the demands of modern education while maintaining spiritual integrity.